Strengthening Vocal Register through Tembang Jawa Ornament Practice - Latifah, Diah (Department of Drama, Dance, and Musik (Sendratasik), Semarang State University, 2015)
This study analyzes Javaneseâs song ornament luk to strengthen vocal register. The movement of luk is either upward or downward has similarity to western vocal techniqueÂ portamento. Portamento ornament is usually used in strengthening the switching technique of vocal register. Register is a vocal technique that has an advantage in maintaining timbre, so that the timbre sounds homogenous when the changing of register occurs. The results of the study show that the Javaneseâs song ornament Luke has successfully strengthened the vocal register on the practice of register intensification in western vocal disciplines.